Invaginating Brown Spot. Issue 5 (September 2016) - Jacob, Sharon E.
Abstract : ABSTRACT: Teledermatology is a term to describe the provision of dermatologic medical services through telecommunication technology. In this modality, there is transfer of medical information electronically (including history and visual data) on a patient in one location to a provider who is in another location. The construct of this column is such that cases are presented in a standardized teledermatology reader format. This is a case of an invaginating brown spot on the thigh.